2022
DOI: 10.1155/2022/2933686
|View full text |Cite|
|
Sign up to set email alerts
|

Three-Dimensional Optimization Development and Regulation of Land Space Based on Spatial Equilibrium Model

Abstract: The territorial space development pattern of the target construction should be able to help the full circulation and optimal allocation of social elements and resources, the society in the region is relatively fair, the development opportunities and welfare of people are equal, and the development of people, society, economy, and environment is coordinated and sustainable. This article aims to develop and control the three-dimensional optimization of the land space based on the spatial equilibrium model. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 27 publications
0
1
0
Order By: Relevance
“…Zhai et al (2022) proposed that the territorial space development pattern of a target construction should be able to support full circulation and optimal allocation of social elements and resources; the society in the region should be relatively fair; development opportunities and people's welfare should be equal; and the development of people, society, economy and environment is coordinated and sustainable. However, the uncertainty of realistic conditions and the complexity of land use systems make it difficult to practice scientific and rational land use planning [13].…”
Section: Introductionmentioning
confidence: 99%
“…Zhai et al (2022) proposed that the territorial space development pattern of a target construction should be able to support full circulation and optimal allocation of social elements and resources; the society in the region should be relatively fair; development opportunities and people's welfare should be equal; and the development of people, society, economy and environment is coordinated and sustainable. However, the uncertainty of realistic conditions and the complexity of land use systems make it difficult to practice scientific and rational land use planning [13].…”
Section: Introductionmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%